Factors that affect the perception of the tourist destination of Braga - Pereira, Manuel Sousa (2022)
This study aims to understand the tourists' perception about the city of Braga (Portugal), bearing in mind four explanatory dimensions for choosing a destination - Destination's Loyalty; Destination's Identity; Destination's Competitiveness and Destinations' Image. This approach introduces a multidimensional concept of a tourist destination as a relationship between tourists and the places they visit. [...]